Prokurator ze skazą. Przyczynki do biografii Henryka Podlaskiego - Kutkowski, Arkadiusz (Komunizm: System - Ludzie - Dokumentacja, 2023)
The article offers insight into Henryk Podlaski, the General Prosecutor’s deputy from 1950 to 1955 (that is the Republic of Poland to 1952 and then the Polish People’s Republic) who was de facto in charge of the General Prosecutor Office’s (GP) Special Department. It was probably the most important department in the entire prosecutorial structure, because it was involved in controlling the investigations conducted by the Ministry of Public Security of Poland (MBP). Podlaski was a controversial figure, considered (especially during the Thaw of 1956) a symbol of the Communist lawlessness, which was a well-deserved characterization since he had been, i.a., one of the creators of the secret jurisdiction in Poland. The author shows subsequent stages of Podlaski’s career in the prosecutorial system: first military, then civilian. The author concludes that the dramatic events of 1956 when, pursued by the judicial authorities reclaiming their subjectivity, he decided to “disappear” from the public life constituted the framing device of his life. Whether the “disappearance” meant a suicide or an escape to the USSR remains unknown. The article is based on the analysis of documents from the Archive of New Records (AAN), the Archive of the Institute of National Remembrance (AIPN), and the proceedings in the legal cases of Roman Romkowski, Anatol Fejgin and Józef Różański.